Change in the Mineral Composition of Mixed Saliva in Patients with Fluorosis, after Applying the Complex of Therapeutic and Prophylactic Measures - Ilyinichna, Ilyinichna (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Scope: In recent decades, the main areas of the research are the issues of prevention and treatment of dental caries. The problem of prevention, diagnosis, and treatment of non-carious diseases continues to be one of the actual and completely unresolved problems of modern dentistry. Materials and Methods: All participants of the study had undergone two procedures of the enamel microabrasion, at interval of a week, using the composition, containing hydrochloric acid, carborundum, and silicone gel. Result and Discussion: As a result of our studies, we found some differences in the mineral composition of mixed saliva, in patients with dental fluorosis after esthetic dental treatment. This plays an important role in the planning of therapeutic and prophylactic measures, aimed at correcting the condition of hard tooth tissues. Conclusion: An important role in the formation and maintenance of enamel resistance is played by the mixed saliva. The daily rhythm of the biochemical parameters of saliva is characterized by a constant content of calcium and phosphorus; that is, important for maintaining the homeostasis of dental tissues. In this connection, we defined the concentration of total and ionized calcium, total phosphate, potassium, magnesium, iron, and chlorides, using the automatic analyzer â€œÐžlimpus,â€ in the samples of mixed saliva of patients with the diseases of hard tooth tissues.